Stress–strain curves and mechanical properties of corrosion damaged super ductile reinforcing steel. (October 2021) - Tariq, Faraz; Bhargava, Pradeep
Highlights: Influence of corrosion on macro structure of Super Ductile Reinforcing Steel bars properties. Influence of corrosion on mechanical properties of Super Ductile Reinforcing Steel bars properties. Influence of corrosion on tensile strength, modulus of elasticity and ductility of Super Ductile Reinforcing Steel bars. Comparison of performance of Corroded Super Ductile Reinforcing Steel over conventional reinforcing steels. Abstract: Super ductile thermo-mechanically treated (SD TMT) reinforcing steel bars are commonly used these days for RC constructions given their excellent thermal and seismic resistant properties. The superior performance of SD TMT rebars is due to their distinct cross-sectional phase distribution (CSPD) of martensite, bainite, and pearlite, which impart better combinations of strength and ductility than conventional classes of steel. This paper presents an investigation carried out to study the influence of corrosion-induced damage to cross-sectional phase distribution (CSPD) on mechanical properties of SD TMT bars in comparison with the performance of conventional mild steel and ordinary TMT steel bars exposed to an aggressive environment. The influence of corrosion-induced damage to cross-sectional phase distribution (CSPD) on the stress–strain response of SD TMT bars has been investigated through tensile tests in a displacement controlled UTM. The study involved tensile tests carried out on SD TMT bars corroded to 25 different levels ranging from (0–45%) on five different rebar diameters (8mmØ, 10mmØ, 12mmØ, 16mmØ and 20mmØ). The results suggest better characteristic performance of SD TMT steel bars over conventional hot-rolled rebars in mechanical behaviour's critical aspects. A correlation predicting the reduction of mechanical properties of corroded TMT bars' residual capacity concerning corrosion percentage has been suggested.